Предмет: Алгебра,
автор: Аноним
Помогите решить (дайте ответ)
Докажите, что значение выражения
(3x-2)(5x-1)-(3x+2)(5x+1)+26x+4
Не зависит от значений x.
Ответы
Автор ответа:
1
Ответ:
(3x-2)(5x-1)-(3x+2)(5x+1)+26x+4 =
= 15x² - 3x -10x + 2 - (15x² + 3x +10x + 2) +26x +4 =
= -3x - 10x -13x +26x +4
Ответ: 4
Объяснение:
-3x -10x -13x = -26x
-26x + 26x сокращается
Похожие вопросы
Предмет: Українська мова,
автор: hm3
Предмет: Химия,
автор: viovioletik
Предмет: Українська мова,
автор: assd228pro1
Предмет: Математика,
автор: sekovenkova80
Предмет: Биология,
автор: sofyatorshina